Safety and efficacy of CT-guided percutaneous microwave ablation for stage I non-small cell lung cancer combined with moderate-to-severe pulmonary dysfunction - Chen, Yuxian; Du, Chengcheng; Li, Chunhai; Meng, Hong; Kong, Fanlei (Frontiers in Oncology, 2026)
IntroductionTo evaluate the safety and efficacy of microwave ablation (MWA) for stage I non-small cell lung cancer (NSCLC) in patients with pulmonary dysfunction.MethodsA retrospective study was conducted involving 1,635 patients who underwent MWA between January 2018 and December 2024. The observation group consisted of 42 patients with moderate-to-severe pulmonary dysfunction, defined as maximal voluntary ventilation (MVV) < 70% or forced expiratory volume in one second (FEV1) < 60%. The control group included 106 patients with normal lung function. The primary study endpoints were postoperative complications and length of hospitalization, while the secondary endpoint was progression-free survival (PFS).ResultsThe observation group had a median follow-up time of 25.5 months and a median survival period of 39 months, with 1-year and 3-year survival rates of 94.9% and 68.7%, respectively. The control group had a median follow-up time of 22 months and a median survival period of 44 months, with 1-year and 3-year survival rates of 98.1% and 72.3%, respectively. The median length of hospitalization was 6 days in both groups. The incidence of adverse reactions was 42.86% in the observation group and 33.96% in the control group, with no statistically significant difference between the two groups (p > 0.4099). In the observation group, statistically significant differences were identified with respect to smoking history, emphysema, and severe pulmonary dysfunction (p < 0.05). Univariate analysis indicated that patients with FEV1 (percentage of predicted value) < 55% and FEV1/VC < 70 were more prone to postoperative complications; however, multivariate analysis revealed no statistically significant differences.DiscussionMWA represents a safe, effective, and potential alternative therapeutic option for patients with stage I NSCLC and moderate-to-severe pulmonary dysfunction.